Analisis Konsumsi Energi Pada Penggunaan Pendingin Udara Kamar Di Patra Jasa Convention Hotel Semarang - Yunanto, Arga Praditya; Adiutomo, Kukup; Hartono, Nugroho; Supriyo, Supriyo (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2014)
which plays an important role in the progress of the economy and the Development of Semarang. Convention Hotel Patra Jasa engaged in recreational services, namely hotel based hall. Lodging and convention hotel in the operational process is not expected to occur interference. Some factors that may affect the operations covered by the hotel is the cost of electricity per month. In this case meant that the use of electricity consumption (Air Conditioning). The method used in the calculation of IKE (Intensity of Energy Consumption). IKE is also used in the calculation method of energy conservation, which can improve the efficiency of energy use .Therefore, it is expected the presence of this study can provide convenience in efficiency savings in the use of IKE particular cooling.